Convenience store woman - Murata, Sayaka 1979- (Granta, 2019)
"Keiko has never really fitted in. At school and university people find her odd and her family worries she'll never be normal. To appease them, Keiko takes a job at a newly opened convenience store. Here, she finds peace and purpose in the simple, daily tasks and routine interactions. She is, she comes to understand, happiest as a convenience store worker. But in Keiko's social circle it just won't do for an unmarried woman to spend all her time stacking shelves and re-ordering green tea. As pressure mounts on Keiko to find either a new job, or worse, a husband, she is forced to take desperate action..."--Provided by publisher